Overproduction and identification of butyrolactones SCB1–8 in the antibiotic production superhost Streptomyces M1152. Issue 27 (16th May 2016) - Sidda, John D.; Poon, Vincent; Song, Lijiang; Wang, Weishan; Yang, Keqian; Corre, Christophe
Abstract : Constitutive production of known and novel butyrolactones SCB1–8 by the bacterial strain Streptomyces coelicolor M1152 is reported. Abstract : Gamma-butyrolactones (GBLs) are signalling molecules that control antibiotic production in Streptomyces bacteria. The genetically engineered strain S. coelicolor M1152 was found to overproduce GBLs SCB1–3 as well as five novel GBLs named SCB4–8. Incorporation experiments using isotopically-labelled precursors confirmed the chemical structures of SCB1–3 and established those of SCB4–8.